Small molecule ISRIB suppresses the integrated stress response within a defined window of activation - Rabouw, Huib H; Langereis, Martijn A; Anand, Aditya A; Visser, Linda J; de Groot, Raoul J; Walter, Peter; van Kuppeveld, Frank J M (Proceedings of the National Academy of Sciences - PNAS, 2019)
Activation of the integrated stress response (ISR) by a variety of stresses triggers phosphorylation of the α-subunit of translation initiation factor eIF2. P-eIF2α inhibits eIF2B, the guanine nucleotide exchange factor that recycles inactive eIF2•GDP to active eIF2•GTP. eIF2 phosphorylation thereby represses translation. Persistent activation of the ISR has been linked to the development of several neurological disorders, and modulation of the ISR promises new therapeutic strategies. Recently, a small-molecule ISR inhibitor (ISRIB) was identified that rescues translation in the presence of P-eIF2α by facilitating the assembly of more active eIF2B. ISRIB enhances cognitive memory processes and has therapeutic effects in brain-injured mice without displaying overt side effects. While using ISRIB to investigate the ISR in picornavirus-infected cells, we observed that ISRIB rescued translation early in infection when P-eIF2α levels were low, but not late in infection when P-eIF2α levels were high. By treating cells with varying concentrations of poly(I:C) or arsenite to induce the ISR, we provide additional proof that ISRIB is unable to inhibit the ISR when intracellular P-eIF2α concentrations exceed a critical threshold level. Together, our data demonstrate that the effects of pharmacological activation of eIF2B are tuned by P-eIF2α concentration. Thus, ISRIB can mitigate undesirable outcomes of low-level ISR activation that may manifest neurological disease but leaves the cytoprotective effects of acute ISR activation intact. The insensitivity of cells to ISRIB during acute ISR may explain why ISRIB does not cause overt toxic side effects in vivo.